Gambaran Pertumbuhan dan Kelangsungan Hidup Lobster Mutiara (Panulirus Ornatus) Di Perairan Mulut Seribu Kabupaten Rote Ndao - Nitti, Trinito Marselino; Sunadji, Sunadji; Liufeto, Franchy Ch (Jurnal Aquatik, 2024)
The cultivation of pearl lobster (Panulirus ornatus) needs to be observed growth rate and survival which can indicate a success rate during rearing. This can be used by the surrounding community as an effort to support the community's economy. To find out the picture of the growth rate, weight, and survival of pearl lobsters cultivated in Thousand Mouth. Observed parameters growth rate, weight and survival of pearl lobster. Observation parameter data in the form of growth, survival and water quality. The data obtained in the form of growth with the results of Baby lobster showed K1 0.072 gs, K2 0.063 gs, K3 0.055 gs, K4 0.057 g and K5 0.074. While the daily growth rate for lobster enlargement is K1 1.356 gs, K2 1.289 g, K3 1.422 g, K4 1.4 g and K5 1.333 g. But at graduation the results of Baby lobster showed K1 95%, K2 95%, K3 96%, K4 98% and K5 55%. While lobsters for rearing maintenance are K1 87%, K2 79%, K3 9%, K4 76% and K5 82%. The results showed that the growth rate of weight / day in lobsters enlargement size was greater than baby lobsters. While baby lobsters have a better survival rate than lobsters of enlargement size, this is due to the nature of cannibalism among adult lobsters when experiencing a moulting period. And the temperature and salinity of seawater still meet the feasible value of pearl lobster cultivation, which is the temperature range during the study of 26-27 ° C, where the minimum temperature value is 26 ° C and the maximum temperature value is 27 ° C. For salinity values ranging from 34-35 ppt, so that the quality of water in the mouth waters of a thousand said is suitable for pearl lobster cultivation. Keywords: Growth, Survival, Pearl Lobster